Optimal state and parameter estimation for a fed-batch induced foreign protein bioreactor - Lee, Jongdae; Ramirez, W. Fred (Zielona Góra: Uniwersytet Zielonogórski)
An extended Kalman filter was used for on-line estimation of system states and parameters for a fed-batch induced foreign protein bioreactor. Simulation work was carried out to test the feasibility of the filter. The extended Kalman filter worked well for state and parameter estimation.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka